2018
DOI: 10.1029/2018jd028908
|View full text |Cite
|
Sign up to set email alerts
|

The Stratospheric Sudden Warming Event in February 2018 and its Prediction by a Climate System Model

Abstract: A major stratospheric sudden warming (SSW) event was observed in February 2018 after a 4-year absence since the winter of 2013/2014. Based on the reanalysis data, the polar night jet changed from a very strong state to a moderate state during 12-19 January, and the moderate westerlies directly reversed to easterlies during 5-15 February. The intensified East Asian trough, Alaskan blocking, and East U.S. trough amplified the extratropical climatological wave 2, which propagated upward into the stratosphere, lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 53 publications
7
92
0
Order By: Relevance
“…To efficiently use and explain the hindcast outputs, statistical error corrections (ECRs) methods based on mathematical modeling are usually necessitated. Rao et al () showed that the predictability of the February 2018 SSW in the BCC_CSM hindcasts was 1 to 2 weeks, which is consistent with the average predictability of SSW events in other models (Karpechko, ; Rao et al, ; Taguchi, , ; Tripathi et al, ). The present paper extends that work by comparing the predictability of 12 SSW events with/without ECRs.…”
Section: Introductionsupporting
confidence: 61%
See 3 more Smart Citations
“…To efficiently use and explain the hindcast outputs, statistical error corrections (ECRs) methods based on mathematical modeling are usually necessitated. Rao et al () showed that the predictability of the February 2018 SSW in the BCC_CSM hindcasts was 1 to 2 weeks, which is consistent with the average predictability of SSW events in other models (Karpechko, ; Rao et al, ; Taguchi, , ; Tripathi et al, ). The present paper extends that work by comparing the predictability of 12 SSW events with/without ECRs.…”
Section: Introductionsupporting
confidence: 61%
“…Every hindcast has four ensemble members, which are produced by a lagged average forecasting strategy with a 6‐hr interval of atmospheric initial conditions ahead. For more details on the model, the reader is directed to Liu et al () and Rao et al (, ).…”
Section: Model Data and Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…The primary definition of a SSW event provided by the World Meteorological Organization requires a stratosphere temperature increase and an accompanying zonal wind reversal to easterlies at the 10 hPa pressure level (approximately 30 km altitude) and 60 • latitude (WMO, 1978). This definition was broadened and detailed in recent papers (Butler et al, 2015;Butler and Gerber, 2018;Rao et al, 2019). The summarizing paper, where a SSW database is described, was published in Butler et al (2017).…”
Section: Introductionmentioning
confidence: 99%